The complete chloroplast genome sequence of Astragalus melilotoides (Fabaceae), a leguminous forage in Northern China - Zhanjun Wang; Ying Tian; Bo Ji; Wangsuo Liu (Mitochondrial DNA. Part B. Resources, 2023)
Astragalus melilotoides Pall. 1776 is a perennial leguminous forage, widely distributed in northern China, with cold, drought and disease resistance characteristics. Here, we determined the complete chloroplast (cp) genome sequence of A. melilotoides. It was 123,827 bp in length and 36.97% GC content with IR loss. The cp genome contained 110 complete genes, including 76 protein-coding genes, 30 tRNA genes, and four rRNA genes. A maximum likelihood (ML) phylogenetic tree revealed that A. melilotoides was related to A. americanus, A. gummifer, A. mongholicus, A. nakaianus, A. mongholicus var. nakaianus, and A. membranaceus var. membranaceus. The cp genome analysis of A. melilotoides will provide a reference for the phylogenetic study of Astragalus in the future.